(untitled) (Clinics, 2017)
OBJECTIVE: To compare the advantages and disadvantages of emergency percutaneous coronary intervention through the left radial artery with those of emergency percutaneous coronary intervention through the femoral artery. METHODS: A total of 206 patients with acute myocardial infarction who required emergency percutaneous coronary intervention and were admitted to our hospital between January 2011 and August 2013 were divided into the following two groups: a group that underwent percutaneous coronary intervention through the left radial artery and a group that underwent percutaneous coronary intervention through the femoral artery. The times required for angiographic catheter and guiding catheter placement, the success rate of the procedure and the incidence of vascular complications in the two groups were observed. RESULTS: There was no significant difference in catheter placement time or the ultimate success rate of the procedure between the two groups. However, the left radial artery group showed a significantly lower incidence of vascular complications than the femoral artery group (p